Analysis of the Effect of Iron Supplementation on Hemoglobin Levels in Adolescent Girls in Mataram City - Cholidah, Rifana; Arnawati, Ida Ayu; Lestarini, Ima Arum; Danianto, Ario; Ayunda, Rahmah Dara (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Anemia remains a chronic nutritional problem in Indonesia, with a relatively high prevalence. According to the 2013 Riskesdas survey, the prevalence of anemia among adolescents aged 15-24 years in Indonesia was 18.4%, which increased to 32% in subsequent years. This means that 3-4 out of 10 adolescents suffer from anemia. Research on the benefits of iron supplementation to reduce the incidence of anemia by increasing hemoglobin levels in adolescent girls has been conducted in several regions in Indonesia. However, similar studies are still rare in NTB, particularly in Mataram City. This study aims to assess the effectiveness of iron supplementation in increasing the hemoglobin levels of adolescent girls in Mataram City. This study is a quasi-experimental research with a one-group pretest and posttest design. The results showed that at the pretest, 58 samples (96.67%) had normal hemoglobin levels, while 2 people (3.33%) had mild anemia. At the posttest, 57 people (95%) had normal hemoglobin levels, 2 people (3.33%) had mild anemia, and 1 person (1.67%) had moderate anemia. The average hemoglobin level at the pretest was 14.47 mg/dl and increased to 14.75 mg/dl six weeks later (posttest). There was no significant difference in hemoglobin levels between the pretest and posttest, with a p-value of 0.210 (p > 0.05).